2000
DOI: 10.1152/ajpregu.2000.278.6.r1564
|View full text |Cite
|
Sign up to set email alerts
|

Bone and shell contribution to lactic acid buffering of submerged turtlesChrysemys picta belliiat 3°C

Abstract: To evaluate shell and bone buffering of lactic acid during acidosis at 3 degrees C, turtles were submerged in anoxic or aerated water and tested at intervals for blood acid-base status and plasma ions and for bone and shell percent water, percent ash, and concentrations of lactate, Ca(2+), Mg(2+), P(i), Na(+), and K(+). After 125 days, plasma lactate concentration rose from 1.6 +/- 0.2 mM (mean +/- SE) to 155.2 +/- 10.8 mM in the anoxic group but only to 25.2 +/- 6.4 mM in the aerated group. The acid-base stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
3
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 25 publications
(28 reference statements)
4
61
3
1
Order By: Relevance
“…This confirms that the observed sequestration by turtle shell and bone is not peculiar to this animal but is very likely a property shared by vertebrate bone generally. In experiments in which turtles were submerged in anoxic water at 3°C for 4·months (Jackson et al, 2000), uptake was not significantly different between skeletal long bone (an endochondral bone) and shell (a largely dermal bone). The difference we observed in the caiman between osteoderm and femur may therefore be due to the short time course of the experiment and slower uptake by long bone.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This confirms that the observed sequestration by turtle shell and bone is not peculiar to this animal but is very likely a property shared by vertebrate bone generally. In experiments in which turtles were submerged in anoxic water at 3°C for 4·months (Jackson et al, 2000), uptake was not significantly different between skeletal long bone (an endochondral bone) and shell (a largely dermal bone). The difference we observed in the caiman between osteoderm and femur may therefore be due to the short time course of the experiment and slower uptake by long bone.…”
Section: Discussionmentioning
confidence: 84%
“…Measured water content of osteoderms was only 30% of bone mass, so equilibrium of dissolved lactate within only the aqueous phase would predict a much lower bone value when expressed per mass of wet bone. As in an earlier analysis of turtle shell and long bone (Jackson et al, 2000), we assume that much of the bone lactate exists in combination with calcium. A rapid equilibration between blood and osteoderms may also explain the relatively high bone lactate values in the 24·h pre-dive control samples.…”
Section: Discussionmentioning
confidence: 99%
“…The turtles were able to extract enough O2 from the water via extrapulmonary mechanisms to remain aerobic throughout their cold submergence, as indicated by their low [lactate]. In contrast, adult C. picta and C. serpentina submerged in normoxic water at 3°C could not extract sufficient O2 to remain entirely aerobic (Ultsch and Jackson, 1982;Jackson et al, 2000;Reese et al, 2002; S. A. Reese, C. E. Crocker, D. C. Jackson and G. R. Ultsch, unpublished data). The ability of hatchlings to remain aerobic during submergence, while their adult conspecifics cannot, may stem from a more favorable surface area to volume ratio, allowing the turtles to extract more O2 per gram of animal, rather than a more favorable metabolic state, since smaller animals typically have a higher mass-specific metabolism (Sievert et al, 1988; D. E. Warren and D. C. Jackson, manuscript submitted for publication), although ontogenetic changes to the diffusion capacity of the gas exchange surfaces (e.g.…”
Section: Physiological Considerationsmentioning
confidence: 99%
“…Denial of oxygen stimulates a physiological switch to anaerobic metabolism, which is characterized by the accumulation of blood lactate and decline in blood pH (Jackson 2000b). Despite having the ability to tolerate true anoxia in cold water, when submerged in elevated normoxic conditions (such as in this study), painted turtles were unable to acquire sufficient oxygen through secondary gas exchange mechanisms to remain aerobic (Ultsch & Jackson 1982, Jackson et al 2000, Reese et al 2001 as indicated in our study by elevated blood lactate and reduced blood pH. Therefore, painted turtles must metabolize energy anaerobically, resulting in blood acidosis (Ultsch & Jackson 1982, Ultsch et al 1999, Jackson et al 2000, Reese et al 2001.…”
Section: A P (C O N T R O L) M a P (T R E A T M E N T ) M A Le (C Omentioning
confidence: 93%
“…Despite having the ability to tolerate true anoxia in cold water, when submerged in elevated normoxic conditions (such as in this study), painted turtles were unable to acquire sufficient oxygen through secondary gas exchange mechanisms to remain aerobic (Ultsch & Jackson 1982, Jackson et al 2000, Reese et al 2001 as indicated in our study by elevated blood lactate and reduced blood pH. Therefore, painted turtles must metabolize energy anaerobically, resulting in blood acidosis (Ultsch & Jackson 1982, Ultsch et al 1999, Jackson et al 2000, Reese et al 2001. Another mechanism of tolerating submergence is the use of gas exchange via extrapulmonary oxygen uptake or bimodal respiration, which is typified by musk and map turtles (Ultsch et al 1984, Reese et al 2001.…”
Section: A P (C O N T R O L) M a P (T R E A T M E N T ) M A Le (C Omentioning
confidence: 94%